Approaches, success factors, and barriers for technology transfer in software engineering—Results of a systematic literature review. Issue 11 (13th August 2018) - Brings, Jennifer; Daun, Marian; Brinckmann, Sarah; Keller, Kevin; Weyer, Thorsten
Abstract: Introduction: Technology transfer aims at supporting the transfer of results from software engineering research from academia to industrial application. Objective: This paper reports on the current state of technology transfer in software engineering. Method: We conducted a systematic literature review, in which we investigated 3070 papers. We identified in total 70 relevant papers, which were subject of a detailed analysis. Results: Many different approaches are proposed to foster technology transfer in software engineering. The majority of these approaches suggest direct collaboration between industry and academia or teaching new technologies in industrial training or university education. In addition, a considerable number of experience reports on technology transfer exist. Hence, a multitude of best practices, success stories, and lessons learned is reported. Among others, empirical evidence, maturity, and adaptability of the technology seem important preconditions for successful transfer, while social and organizational factors seem important barriers to successful technology transfer. Conclusion: Our findings can aid software engineering researchers in determining how best to support the transfer of their research results into practice. Furthermore, analysis of the literature also revealed that no reports exist on the combination of various technology transfer approaches, which could increase advantages of existing approaches while reducing their disadvantages. Abstract : Technology transfer aims at supporting the transfer of results from software engineering research from academia to industrial application. Results from a systematic literature review of technology transfer research in software engineering show a variety of suggested transfer approaches and point to success factors and barriers for technology transfer in software engineering. Our findings aid software engineering researcher in determining how best to support the transfer of their research results into practice.